Gender Differences in Meaningful Leisure Among Older Adults: Joint Displays of Four Phenomena - Jaumot-Pascual, Nuria; Monteagudo, María Jesús; Kleiber, Douglas A.; Cuenca, Jaime (Frontiers in Psychology, 2018)
Vital events, such as widowhood and retirement, are broadly accepted as points of inflection in the lives of older adults that often differ according to gender. In this study, we analyzed the influence of gender differences in meaningful leisure among older adults through the integration of qualitative and quantitative findings. The use of joint displays revealed that: (1) there is no significant difference between the influence of retirement and widowhood on the two genders, (2) the ethic of care is a constraining factor in older women’s leisure, (3) women are more innovative in their leisure in older age, and (4) volunteer activities are highly segregated by gender. The use of joint displays helped illuminate these four phenomena in light of quantitative and qualitative data.